Creativity and Learning in Citizen Cyberscience – Lessons from the Citizen Cyberlab Summit - Ramanauskaitė, Eglė Marija; Haklay, Mordechai (Human Computation, 2016)
This article summarizes the Citizen Cyberlab (CCL) Summit, which took place at University of Geneva on 17-18th September 2015, and introduces the special issue on “Learning and Creativity in Citizen Science”. As the final event of a 3-year EU FP7 CCL project, the Summit sought to disseminate project results and reflect on the issue of citizen science (CS) as a participatory environment where opportunities for self-development and various types of creativity can arise. A number of interesting themes emerged at the intersection of the work presented by project collaborators and external partners, including the different types of creativity that are evident in CS, the role of the community as the main medium for innovation and participant learning to occur, and the common challenges concerning the design, initiation and management of CS projects. The current issue presents work done during the CCL project, as well as external project contributions, for which the main focus is on learning and creativity in CS. The set of articles addresses diverse aspects of the topic, ranging from empirical research on the phenomena themselves, to tools, platforms and frameworks developed specifically for citizen cyberscience (CCS) with creativity and learning in mind, and distinct CS cases where these phenomena manifest in previously undescribed and unexpected ways. We hope that the issue will be useful to researchers and practitioners who aim to study, evaluate or design for learning and creativity in a range of CCS projects.